Nationalism, Patriotism and Political Ideas of Sir Syed Ahmad Khan: an Analysis - Tanjeel Ahmed; Muhammad Amin (International Journal Ihya' 'Ulum al-Din, 2021)
Sir Syed Ahmad Khan (Founder of Aligarh Muslim University) was born into a noble Muslim family in 1817; he was a distinguished scholar while working as a lawyer at the British East India Company. After realizing the worthless condition of Muslims, his approach to western education for the benefit of the Muslim community became a priority. This study contemplates that Sir Syed was religiously oriented and very politically aware of nationalism and patriotism. The author uses primary data and also secondary data. The author also explores his main books and articles; the author aims to examine Sir Syed's nationalist and political ideas concerning political significance for Muslims in India. The writer would like to know the result that, what is the reason, Sir Syed was against the Indian National Congress. At the same time, the whole Indian society was afraid of the British, but Sir Syed maintained his good relations with the British, and he also showed the loyalty of the Muslims towards them. This study found the conclusion about Sir Syed that he became a symbol of communal harmony.